2018
DOI: 10.1016/j.jcrs.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Iris-claw intraocular lens for aphakia: Can location influence the final outcomes?

Abstract: Irrespective of location, the iris-claw IOL provided good visual outcomes with few complications. However, prepupillary IOL implantation seemed to contribute to greater endothelial cell loss and earlier onset of CME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 19 publications
2
84
0
9
Order By: Relevance
“…; Peralba et al. ; Rastogi et al. ) and are most commonly attributed to steroid response, anterior chamber inflammation, retained viscoelastic in the anterior chamber and pigment dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Peralba et al. ; Rastogi et al. ) and are most commonly attributed to steroid response, anterior chamber inflammation, retained viscoelastic in the anterior chamber and pigment dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Peralba and co‐authors found the incidence of cystoid macular oedema to be more common and to occur earlier in prepupillary compared to retropupillary iris‐claw lenses (Peralba et al. ). There was a slight but statistical increase in the central foveal thickness, measured by OCT in both groups, but no cases of cystoid macular oedema or clinical oedema on biomicroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Частота основных осложнений, таких как гипертензия и вторичная глаукома, хронический увеит, буллезная дистрофия роговицы, -существенно ниже при фиксации ирискло ИОЛ за радужкой [4,[29][30][31][32][33][34]. Результаты специального сравнительного исследования показали снижение частоты макулярного отека в среднем в 3 раза при ретропупиллярной фиксации современных ирискло линз по сравнению с препупиллярной имплантацией аналогичных ИОЛ [35].…”
Section: обзоры литературыunclassified
“…Интраоперационный выброс простагландинов, развитие хронического увеита, отсутствие капсулярного барьера, наличие тракционного синдрома провоцируют возникновение отека макулы, который, как правило, развивается после транссклеральной ретропупиллярной фиксации реже по сравнению с переднекамерной и зрачковой фиксацией ИОЛ. Частота отека макулы с клиническими проявлениями (снижением остроты зрения) после внекапсульной имплантации современных ретропупиллярных ИОЛ, по данным большинства исследований, составляет менее 10% [25,35]. Ретропупиллярная фиксация современных ирис-кло линз (Артисан) в 3 раза реже сопровождается возникновением отека макулы в послеоперационном периоде по сравнению с препупиллярной фиксацией этой же модели [35].…”
Section: обзоры литературыunclassified
See 1 more Smart Citation